2023
DOI: 10.3389/fpsyt.2023.1140597
|View full text |Cite
|
Sign up to set email alerts
|

Association between life events, anxiety, depression and non-suicidal self-injury behavior in Chinese psychiatric adolescent inpatients: a cross-sectional study

Abstract: BackgroundNon-suicidal self-injury (NSSI) is a major public health concern among adolescents. Further research is needed into contributors to this behavior, in particular among adolescents with psychiatric disorders. The aim of the present study was to explore the impact of life events and emotional stress on NSSI among hospitalized psychiatric adolescents.MethodsIn this cross-sectional study, 505 Chinese psychiatric adolescent inpatients 10–19  years old completed questionnaires about sociodemographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Of the 1299 participants, there were 607 (46.7%) males and 692 (53.3%) females aged 12-18 years old (mean: 15.33±1.51 years). At the time of data collection, there were 566 (45.1%) junior middle school students (grades 7, 8, 9), and 733 (54.9%) high middle school students (grades 10,11,12). The results of the Chi-square test showed high middle school students were more inclined to be involved in NSSI than participants of junior middle school (p = 0.03).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 1299 participants, there were 607 (46.7%) males and 692 (53.3%) females aged 12-18 years old (mean: 15.33±1.51 years). At the time of data collection, there were 566 (45.1%) junior middle school students (grades 7, 8, 9), and 733 (54.9%) high middle school students (grades 10,11,12). The results of the Chi-square test showed high middle school students were more inclined to be involved in NSSI than participants of junior middle school (p = 0.03).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…There have been reports of higher rates among psychiatric adolescent inpatients, which exceed 40%. [9][10][11] Non-suicidal self-injury seriously affects the physical and mental health of adolescents as it is associated with greater psychosocial functioning impairment, 12 higher levels of depression and anxiety, 13 impulsivity, 14 and suicide attempts. 15 Due to rapid physiological and psychological changes, adolescents are most intensely influenced by negative peer relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The detection rate of depression among NSSI patients was as high as 81.3%. 18 It has been reported that compared to simple depression, comorbidity will characterize more severe clinical phenotypes in adolescents, aggravate the psychological and disease burden of patients, and increase the risk of suicide. 19 Previous research on comorbidity of NSSI and depression in adolescents had focused on correlates, such as introversion, intermediate defenses, 20 youthfulness, and impulsivity, 21 but the specific symptoms underlying this correlation are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 1 NSSI is common in adolescents, usually in mid-adolescence (about 14-16 years old), 2 and manifests as scratching the skin, cutting the wrist, pulling the hair, banging the head, and scalding. 3 Adolescent NSSI behavior is a worldwide concern, and its incidence varies widely among different countries and regions. Indeed, it has become a social public-health problem affecting the mental health of adolescents.…”
Section: Introductionmentioning
confidence: 99%